Digital enlightenment yearbook 2013 : the value of personal data - Hildebrandt, Mireille; O'Hara, Kieron; Waidner, Michael (Digital enlightenment yearbook, 2013)
The value of personal data has traditionally been understood in ethical terms as a safeguard for personality rights such as human dignity and privacy. However, we have entered an era where personal data are mined, traded and monetized in the process of creating added value - often in terms of free services including efficient search, support for social networking and personalized communications. This volume investigates whether the economic value of personal data can be realized without compromising privacy, fairness and contextual integrity. It brings scholars and scientists from the discipli.